SISTEM INFORMASI PENGIRIMAN BARANG - Raihan Zhafar (Information Technology Studies Journal (ITECH), 2024)
The aim of writing this final assignment is to design a web-based goods delivery information system to make it easier for the admin, warehouse department and finance department to make reports. The program used in writing this final assignment is web-based which uses PHP as the database and XAMPP as the link. This web-based goods delivery information system emerged when the author made observations, so it is hoped that this goods delivery information system can help the admin, warehouse and finance departments and provide the best solution for the company.  The results of this program show that the software with a connected database can store various archives and information needed. This application includes a goods delivery system, placement of goods in the warehouse and reports that can be transferred to Excel.